Madinan Society at the Time of the Prophet: its Characteristics and Organization = Masyarakat Madani : Tinjauan Historis Kehidupan Zaman Nabi - Akram Dhiyauddin Umari (Gema Insani Press, 1999)
170 hal.; 24 cm.